Dirhodium(II)-catalyzed [3 + 2] cycloaddition of N-arylaminocyclopropane with alkyne derivatives - Liu, Wentong; Kuang, Yi; Wang, Zhifan; Zhu, Jin; Wang, Yuanhua (Beilstein Journal of Organic Chemistry, 2019)
Dirhodium(II) complex-catalyzed [3 + 2] reactions between N-arylaminocyclopropanes and alkyne derivatives are described. The cycloaddition products proved to be versatile synthetic intermediates. trans-Cyclic β-amino acids and derivatives thereof can be conveniently synthesized using this cycloaddition protocol.
Keywords: [3 + 2]; alkyne; cycloaddition; cyclopropanes; dirhodium catalysis; N-arylaminocyclopropanes

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Garg, R.; Gupta, S. P.; Gao, H.; Babu, M. S.; Debnath, A. K.; Hansch, C. (Chem. Rev., 1999)

(untitled) - Jiao, L.; Yu, Z.-X. (J. Org. Chem., 2013)

(untitled) - Schneider, T. F.; Kaschel, J.; Werz, D. B. (Angew. Chem., Int. Ed., 2014)

(untitled) - Gao, Y.; Fu, X.-F.; Yu, Z.-X. (Top. Curr. Chem., 2014)

(untitled) - Grover, H. K.; Emmett, M. R.; Kerr, M. A. (Org. Biomol. Chem., 2015)

(untitled) - Maity, S.; Zhu, M.; Shinabery, R. S.; Zheng, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Maity, S.; Zheng, N. (Synlett, 2012)

(untitled) - Hu, J.; Wang, J.; Nguyen, T. H.; Zheng, N. (Beilstein J. Org. Chem., 2013)

(untitled) - Nguyen, T. H.; Maity, S.; Zheng, N. (Beilstein J. Org. Chem., 2014)

(untitled) - Nguyen, T. H.; Morris, S. A.; Zheng, N. (Adv. Synth. Catal., 2014)

(untitled) - Morris, S. A.; Wang, J.; Zheng, N. (Acc. Chem. Res., 2016)

(untitled) - Cai, Y.; Wang, J.; Zhang, Y.; Li, Z.; Hu, D.; Zheng, N.; Chen, H. (J. Am. Chem. Soc., 2017)

(untitled) - Wimalasena, K.; Wickman, H. B.; Mahindaratne, M. P. D. (Eur. J. Org. Chem., 2001)

(untitled) - Blackburn, A.; Bowles, D. M.; Curran, T. T.; Kim, H. (Synth. Commun., 2012)

(untitled) - Gildner, P. G.; DeAngelis, A.; Colacot, T. J. (Org. Lett., 2016)

(untitled) - Tassone, J. P.; MacQueen, P. M.; Lavoie, C. M.; Ferguson, M. J.; McDonald, R.; Stradiotto, M. (ACS Catal., 2017)

(untitled) - Kuang, Y.; Ning, Y.; Zhu, J.; Wang, Y. (Org. Lett., 2018)

(untitled) - Wang, Y.; Wolf, J.; Zavalij, P.; Doyle, M. P. (Angew. Chem., Int. Ed., 2008)

(untitled) - Xu, X.; Wang, X.; Liu, Y.; Doyle, M. P. (J. Org. Chem., 2014)

(untitled) - Lucarini, M.; Pedulli, G. F. (Chem. Soc. Rev., 2010)

(untitled) - Giese, B.; Lachhein, S. (Angew. Chem., Int. Ed. Engl., 1982)

(untitled) - Fischer, H.; Radom, L. (Angew. Chem., Int. Ed., 2001)

(untitled) - Wille, U. (Chem. Rev., 2013)

(untitled) - Gellman, S. H. (Acc. Chem. Res., 1998)

(untitled) - Seebach, D.; Matthews, J. L. (Chem. Commun., 1997)

(untitled) - Seebach, D.; Abele, S.; Gademann, K.; Guichard, G.; Hintermann, T.; Jaun, B.; Matthews, J. L.; Schreiber, J. V.; Oberer, L.; Hommel, U.; Widmer, H. (Helv. Chim. Acta, 1998)

(untitled) - Davies, H. M. L.; Venkataramani, C. (Angew. Chem., Int. Ed., 2002)

(untitled) - Tang, W.; Wu, S.; Zhang, X. (J. Am. Chem. Soc., 2003)